New Two-Dimensional Polynomial Failure Criteria for Composite Materials - Shi Yang Zhao; Pu Xue (Advances in Materials Science and Engineering)
The in-plane damage behavior and material properties of the composite material are very complex. At present, a large number of two-dimensional failure criteria, such as Chang-Chang criteria, have been proposed to predict the damage process of composite structures under loading. However, there is still no good criterion to realize it with both enough accuracy and computational performance. All these criteria cannot be adjusted by experimental data. Therefore, any special properties of composite material cannot be considered by these criteria. Here, in order to solve the problem that the criteria cannot be adjusted by experiment, new two-dimensional polynomial failure criteria with four internal parameters for composite laminates are proposed in the paper, which include four distinct failure modes: fiber tensile failure, fiber compressive failure, matrix tensile failure, and matrix compressive failure. In general, the four internal parameters should be determined by experiments. One example that identifies parameters of the new failure criteria is given. Using the new criteria can reduce the artificialness of choosing the criteria for the damage simulation of the failure modes in composite laminates.